(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to reveal the degree to which teachers of Arabic language and social studies practice the skills of the twenty-first century in Karak Governorate. The study sample consisted of (329) male and female teachers from the Directorate of Education of Karak Governorate. The sample was selected by a random stratified method, and the descriptive survey method was used. To achieve the goals of the study, the researchers develeoped a survey that covered four domains: (i) critical thinking skills, problem solving, and creativity, (ii) social and communication skills, (iii) information and digital culture, and initiative, self-direction and responsibility. After verifying the validity and reliability of the tool, it was applied on the study sample. The results showed that teachers’ ratings on the four fields of study were moderate; the field of critical thinking, problem solving and creativity ranked first with an arithmetic mean of (2.75) and a standard deviation of (.257), while the field of information and digital culture achieved the least estimate, with an arithmetic mean of (2.48) and a standard deviation of (.370). The results also showed that there were no statistically significant differences due to the variables of gender, academic level, and scientific specialization. The study recommended holding training courses for teachers to provide them with the skills of the twenty-first century.